SOSIALISASI MENGENAI PENCEGAHAN BULLYING UNTUK MENINGKATKAN INTERAKSI YANG BAIK ANTARA SISWA DI SEKOLAH SDN 1 SINGAPADU KALER - I Gusti Bagus Wahyu Nugraha Putra; I Wayan Juniartha; I Komang Sulatra; Ni Kadek Tita; Ni Kadek Parian Dewi (LOKATARA SARASWATI, 2025)
This Student Creativity Program (PKM) aims to improve elementary school students’ understanding of the importance of early bullying prevention. The activity was conducted at SDN 1 Singapadu Kaler, Gianyar, Bali, targeting first and second-grade students. Initial observations revealed that students had limited knowledge about bullying. To address this, an educational approach was implemented using interactive methods such as video screenings, group discussions, and role-playing. A descriptive qualitative method was used, with data collected through observation, teacher interviews, and simple pre- and post-tests. The results showed a 35% increase in student understanding and a stronger attitude in rejecting bullying behavior. This program contributed to fostering a safer school environment and strengthening positive character from an early age.